Proving The Crime Of Money Laundering In Corruption Cases - Dharen, Sri; Shodiq, Md.; Pomsen , Chanida (CV. Era Digital Nusantara, 2024)
This research aims to analyse the mechanism of proof of money laundering crime (TPPU) originating from the proceeds of corruption in Indonesia. One of the main focuses in this research is the application of the reversal of the burden of proof system stipulated in Law Number 8 Year 2010 on the Prevention and Eradication of Money Laundering Crimes (Anti-Money Laundering Law). This research hypothesis argues that the reversal of the burden of proof system can be an effective instrument in proving money laundering crimes originating from corruption, by utilising the role of financial institutions, transaction analysis by PPATK, and synergy between law enforcement officials. The research method used is juridical-normative with an analytical descriptive approach, which examines the applicable legislation, as well as the practice of its application in the Indonesian judicial system. The results show that despite technical obstacles in proof, such as difficulties in tracing the origin of laundered assets, the application of reversal of the burden of proof provides significant advantages for law enforcement. It is hoped that the application of strict sanctions against ML offenders can provide a deterrent effect while increasing the effectiveness of corruption eradication in Indonesia.